Crafting and executing strategy the quest for competitive advantage : concepts and cases - Thompson, Arthur A.
The distinguishing mark of the 19th edition is its enriched and enlivened presentation of the material in each of the 12 chapters, providing an as up-to-date and engrossing discussion of the core concepts and analytical tools as you will find anywhere. There is an accompanying line-up of exciting new cases that bring the content to life and are sure to provoke interesting classroom discussions, deepening students' understanding of the material in the process. While this 19th edition retains the 12-chapter structure of the prior edition, every chapter -indeed every paragraph and every line - has been re-examined, refined, and refreshed. New content has been added to keep the material in line with the latest developments in the theory and practice of strategic management. In other areas, coverage has been trimmed to keep the book at a more manageable size. Scores of new examples have been added, along with 16 new Illustration Capsules, to enrich understanding of the content and to provide students with a ringside view of strategy in action. The result is a text that cuts straight to the chase in terms of what students really need to know and gives instructors a leg up on teaching that material effectively. It remains, as always, solidly mainstream and balanced, mirroring both the penetrating insight of academic thought and the pragmatism of real-world strategic management.